Point-of-care HIV viral load testing combined with task shifting to improve treatment outcomes (STREAM): findings from an open-label, non-inferiority, randomised controlled trial. Issue 4 (April 2020) - Drain, Paul K; Dorward, Jienchi; Violette, Lauren R; Quame-Amaglo, Justice; Thomas, Katherine K; Samsunder, Natasha; Ngobese, Hope; Mlisana, Koleka; Moodley, Pravikrishnen; Donnell, Deborah; Barnabas, Ruanne V; Naidoo, Kogieleum; et al.
Summary: Background: Monitoring HIV treatment with laboratory testing introduces delays for providing appropriate care in resource-limited settings. The aim of our study was to determine whether point-of-care HIV viral load testing with task shifting changed treatment and care outcomes for adults on antiretroviral therapy (ART) when compared with standard laboratory viral load testing. Methods: We did an open-label, non-inferiority, randomised controlled trial in a public clinic in Durban, South Africa. We enrolled HIV-positive adults (aged ≥18 years) who presented for their first routine HIV viral load test 6 months after ART initiation. Individuals were randomly assigned by a random number allocation sequence to receive either point-of-care viral load testing at enrolment and after 6 months with task shifting to enrolled nurses (intervention group), or laboratory viral load testing (standard-of-care group). The primary outcome was combined viral suppression (<200 copies per mL) and retention at 12 months after enrolment. A non-inferiority margin of 10% was used. Analysis was done by intention to treat. This study was registered with ClinicalTrials.gov, NCT03066128 . Findings: Between Feb 24, 2017, and Aug 23, 2017, we screened 657 participants, and 390 were enrolled and randomly assigned to either the intervention group (n=195) or standard-of-care group (n=195). 175 (90%) individuals in the intervention group and 148 (76%) individuals in the standard-of-care group had the primary outcome of retention with viral suppression, a difference of 13·9% (95% CI 6·4–21·2; p<0·00040). 182 participants (93%) in the intervention group had viral suppression compared with 162 (83%) in the standard-of-care group (difference 10·3%, 3·9–16·8; p=0·0025); 180 (92%) and 162 (85%) were retained in care (7·7%, 1·3–14·2; p=0·026). There were no adverse events related to point-of-care HIV viral load testing or task shifting. Interpretation: Point-of-care viral load testing combined with task shifting significantly improved viral suppression and retention in HIV care. Point-of-care testing can simplify treatment and improve outcomes for HIV-positive adults receiving ART in resource-limited settings. Funding: National Institute of Allergy and Infectious Diseases.